2016
DOI: 10.1016/j.cviu.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A generalized graph reduction framework for interactive segmentation of large images

Abstract: The speed of graph-based segmentation approaches, such as random walker (RW) and graph cut (GC), depends strongly on image size. For high-resolution images, the time required to compute a segmentation based on user input renders interaction tedious. We propose a novel method, using an approximate contour sketched by the user, to reduce the graph before passing it on to a segmentation algorithm such as RW or GC. This enables a significantly faster feedback loop. The user first draws a rough contour of the objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…this study was 100 ms. Therefore, the segmentation method must satisfy this threshold, i.e., provide updates under 100 ms. To achieve this, we developed the FastDRaW 2 method [10], a fast adaptation of the random walker segmentation algorithm [9]. FastDRaW exploits a multi-scale framework combined with a dynamic region of interest (ROI) search to reduce the computation time.…”
Section: E Segmentation Methods and Computationsmentioning
confidence: 99%
See 2 more Smart Citations
“…this study was 100 ms. Therefore, the segmentation method must satisfy this threshold, i.e., provide updates under 100 ms. To achieve this, we developed the FastDRaW 2 method [10], a fast adaptation of the random walker segmentation algorithm [9]. FastDRaW exploits a multi-scale framework combined with a dynamic region of interest (ROI) search to reduce the computation time.…”
Section: E Segmentation Methods and Computationsmentioning
confidence: 99%
“…Previous evaluations of interactive segmentation have focused on algorithmic runtime, with few studies of human factors. One preliminary study [10] found that improvements in computational performance did not yield a commensurate improvement in overall segmentation performance, i.e, the total time including user actions. Although computation time was improved by a factor ∼ 10 (from 1.23 s to 0.13 s), overall segmentation time was only improved by a factor ∼ 2 (from 25.25 s to 17.08 s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different interactive segmentation algorithms employ different superpixel algorithms of varying sizes. For instance, [6] and [7] used the SLIC superpixel algorithm [8] with 1000 and 2000 superpixels superpixel per image, respectively. In addition, [9] used a meant-shift superpixel algorithm with 100 superpixels per image.…”
Section: Introductionmentioning
confidence: 99%
“…The two most common application scopes for these kinds of algorithms are segmentation of a particular anatomic structure in medical imagery [5][6][7][8][9][10][11][12][13][14] and natural photograph (such as an image taken with a smartphone or a camera) manipulation for art or graphic design purpose. [15][16][17][18][19][20][21][22][23][24][25][26] These two application scopes correspond to distinct problems, with substantial differences among proceeded image features and the available prior information.…”
Section: Introductionmentioning
confidence: 99%